A systemic view of potential environmental impacts of ocean energy production. (October 2021) - Martínez, M.L.; Vázquez, G.; Pérez-Maqueo, O.; Silva, R.; Moreno-Casasola, P.; Mendoza-González, G.; López-Portillo, J.; MacGregor-Fors, I.; Heckel, G.; Hernández-Santana, J.R.; García-Franco, J.G.; Castillo-Campos, G.; et al.
Abstract: Renewable ocean energy is an alternative that will help reduce carbon emissions into the atmosphere. However, there is uncertainty about potential environmental impacts of the technologies involved, because these are new and untested, and methods for the evaluation and monitoring of environmental impacts are scarce. We performed a systematic literature review (well-structured and organized, always looking for the same terms), followed by a systemic analysis in which we considered the interactions between environmental stressors, effects, receptors, and their responses. We found that most studies are theoretical revisions and modelling exercises, although field and laboratory experiments and observations are beginning to accumulate. Environmental stressors are features in the environment (energy-harvesting devices) that modify the natural dynamics of the system. The effects are the changes in the environment induced by the stressors; the most frequently acknowledged and measured are noise, collision, habitat change, hydro-sedimentary dynamics and wave modifications. The receptors of these changes are marine fauna, such as mammals, fish, sea birds, and benthic communities, as well as the shoreline. Their corresponding responses include behaviour, injuries/death, biodiversity loss, alterations in food webs and shoreline change. Once the different components of the environmental impacts are identified, it is important to develop monitoring and mitigation strategies to prevent, or minimize, environmental damage. Ocean energy is a promising option to reduce CO2 emissions into the atmosphere, but the implementation of adequate monitoring and mitigation technologies requires multidisciplinary efforts to obtain effectively clean, renewable energy and to maintain healthy and functional ecosystems. Highlights: We review the scientific literature focused on the environmental impacts of MRE (Marine Renewable Energy). A systems-thinking approach identified stressors, effects, receptors, and responses. Several information gaps were found through the revision of the literature. Experimental and field evidence is necessary to assess impacts quantitatively. Multidisciplinary monitoring and mitigation strategies should be followed.